POLISEMI DALAM BAHASA JAWA DIALEK BANYUMAS - Purwani, Rina (Jurnal Ilmiah Bina Bahasa, 2020)
This research aimed to describe types of polysemy and the effects of how polysemy is formed in Banyumas regional society. This search is descriptive qualitative and the data were words that often communicate by Banyumas community. Data analysis resulted that polysemy in Banyumas region in term of part of speech can be divided into there types namely (1) noun, (2) verbs, and (3) adjectives. The verb is the most dominating polysemy type. Those three types of polysemy then were grouped into two forms namely (1) basic polysemy, and (2) derivative polysemy. The derived polysemy was grouped into three; derivative polysemy with an affix, duplicate derived polysemy, and derived polysemy of the combined process. Then a derivative noun polysemic with the suffix {ne-} is found. Derivative verb polysemy is affixed with prefix {di-} and prefix N-, and with the confix {ke- + KD + -an}.